2015
DOI: 10.1007/s10592-015-0731-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene dynamics of toll-like receptor 4 through a population bottleneck in an insular population of water voles (Arvicola amphibius)

Abstract: Understanding the extent to which diversity at immunologically important genes is reduced by demographic perturbations such as population bottlenecks, and the resulting consequences this has on individual fitness, is of fundamental importance for the effective management of genetic resources in natural populations. Toll-like receptors are key immunological genes with well-established links to fitness. Here, levels of allelic diversity and heterozygosity at the toll-like receptor 4 locus (Tlr4) were characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…Clinical studies have shown that polymorphism within TLR genes, particularly in the part of the molecule interacting with PAMP, affects susceptibility to diseases in humans – for instance, a single nucleotide polymorphism (SNP) in the TLR2 gene has been attributed to susceptibility to tuberculosis, cytomeglaovirus, and borreliosis, whereas SNPs associated with susceptibility to hepatitis C virus have been identified in TLR7 (see the work reviewed in 6 ). Associations between TLR variants and susceptibility have also recently been found in TLR2 and TLR4 4 , 7 in free living species.…”
Section: Introductionmentioning
confidence: 81%
“…Clinical studies have shown that polymorphism within TLR genes, particularly in the part of the molecule interacting with PAMP, affects susceptibility to diseases in humans – for instance, a single nucleotide polymorphism (SNP) in the TLR2 gene has been attributed to susceptibility to tuberculosis, cytomeglaovirus, and borreliosis, whereas SNPs associated with susceptibility to hepatitis C virus have been identified in TLR7 (see the work reviewed in 6 ). Associations between TLR variants and susceptibility have also recently been found in TLR2 and TLR4 4 , 7 in free living species.…”
Section: Introductionmentioning
confidence: 81%
“…The genetic basis of parasite susceptibility has been notoriously difficult to uncover (Wilfert & Schmid‐Hempel, ), although some insight has been gained through bottom‐up candidate gene approaches involving MHC (e.g. Oliver et al ., ; Oppelt et al ., ; Sin et al ., ), interferon‐gamma (Coltman et al ., ; Stear et al ., ), Toll‐like receptors (Downing et al ., ; Gavan et al ., ) and cytokines (Luikart et al ., ; Downing et al ., ; Turner et al ., ). Landscape‐scale application of novel top‐down candidate genes for parasite susceptibility in Daphnia revealed differential patterns of selection at these genes among populations in different stress environments, but no conclusive associations between allele frequencies and parasite prevalence were found (Orsini et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…These effects may be underpinned by substantial numbers of genes with small individual effect sizes (Wilfert & Schmid‐Hempel, ; Rockman, ). Although heritability of parasite susceptibility and tolerance is well documented (Gauly & Erhardt, ; Stear et al ., ; Mazé‐Guilmo et al ., ) and a range of bottom‐up candidate immune system genes, such as the MHC (Oliver et al ., ; Oppelt et al ., ; Sin et al ., ), interferon‐gamma (Coltman et al ., ; Stear et al ., ), Toll‐like receptors (Downing et al ., ; Gavan et al ., ) and cytokines (Luikart et al ., ; Downing et al ., ; Turner et al ., ), have provided some insight, identification of novel top‐down candidate genes for parasite infection in animals beyond immune system genes has proved to be a major challenge. For example, no conclusive associations between candidate gene allele frequencies and parasite prevalence were found in Daphnia (Orsini et al ., ) and Soay sheep populations (Brown et al ., ), despite employing transcriptomic assays for gene discovery (Orsini et al ., ; Pemberton et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a greater proportion of phenotypic variance in malaria response has been attributed to non-MHC genes (Jepson et al, 1997). Within the innate immune system (a first line of defense against infection), Toll-like receptors (TLRs) are a family of pattern-recognition receptors which have been linked to malaria resistance (Ferwerda et al, 2007;Mockenhaupt et al, 2006), and show evidence of pathogen-mediated balancing selection (Ferrer-Admetlla et al, 2008;Fisher et al, 2011;Gavan, Oliver, Douglas, & Piertney, 2015). TLRs therefore represent important candidates for investigating the role of pathogens in maintaining host genetic variation.…”
Section: Introductionmentioning
confidence: 99%